Increased localized delivery of piroxicam by cationic nanoparticles after intra-articular injection - Kim SR; Ho MJ; Kim SH; Cho HR; Kim HS; Choi YS; Choi YW; Kang MJ (Dove Medical Press, 2016)
Sung Rae Kim,1 Myoung Jin Ho,2 Sang Hyun Kim,1 Ha Ra Cho,2 Han Sol Kim,2 Yong Seok Choi,2 Young Wook Choi,1 Myung Joo Kang2 1Division of Pharmaceutical Sciences, College of Pharmacy, Chung-Ang University, Seoul, 2College of Pharmacy, Dankook University, Cheonan, Chungnam, South Korea Abstract: Piroxicam (PRX), a potent nonsteroidal anti-inflammatory drug, is prescribed to relieve postoperative and/or chronic joint pain. However, its oral administration often results in serious gastrointestinal adverse effects including duodenal ulceration. Thus, a novel cationic nanoparticle (NP) was explored to minimize the systemic exposure and increase the retention time of PRX in the joint after intra-articular (IA) injection, by forming micrometer-sized electrostatic clusters with endogenous hyaluronic acid (HA) in the synovial cavity. PRX-loaded NPs consisting of poly(lactic-co-glycolic acid), Eudragit RL, and polyvinyl alcohol were constructed with the following characteristics: particle size of 220 nm, zeta potential of 11.5 mV in phosphate-buffered saline, and loading amount of 4.0% (w/w) of PRX. In optical and hyperspectral observations, the cationic NPs formed more than 50 µm-sized aggregates with HA, which was larger than the intercellular gaps between synoviocytes. In an in vivo pharmacokinetic study in rats, area under the plasma concentration–time curve (AUC0–24 h) and maximum plasma concentration (Cmax) of PRX after IA injection of the cationic NPs were <70% (P<0.05) and 60% (P<0.05), respectively, compared to those obtained from drug solution. Moreover, the drug concentration in joint tissue 24 h after dosing with the cationic NPs was 3.2-fold (P<0.05) and 1.8-fold (P<0.05) higher than that from drug solution and neutrally charged NPs, respectively. Therefore, we recommend the IA cationic NP therapy as an effective alternative to traditional oral therapy with PRX, as it increases drug retention selectively in the joint. Keywords: piroxicam, polymeric nanoparticles, electrostatic interaction, intra-articular injection, local delivery, hyaluronic acid